2016
DOI: 10.1016/j.radonc.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Conformity analysis to demonstrate reproducibility of target volumes for Margin-Intense Stereotactic Radiotherapy for borderline-resectable pancreatic cancer

Abstract: Background and purposeMargin-directed neoadjuvant radiotherapy for borderline-resectable pancreatic cancer (BRPC) aims to facilitate clear surgical margins. A systematic method was developed for definition of a boost target volume prior to a formal phase-I study.Material and methodsReference structures were defined by two oncologists and one radiologist, target structures were submitted by eight oncologist investigators and compared using conformity indices. Resultant risk of duodenal bleed (NTCP) was modelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In addition, the inclusion of margin intensive boost yielded mostly equivalent results to Boost2, indicating that a boosting dose (40 Gy) to the margin of involved vasculature does not substantially increase GI‐OAR doses if the boosting area is away from GI‐OARs (1 cm in the current study). This result agrees with recent investigations on this strategy, opening the way for achieving a greater regression in this critical area of the tumor …”
Section: Discussionsupporting
confidence: 93%
“…In addition, the inclusion of margin intensive boost yielded mostly equivalent results to Boost2, indicating that a boosting dose (40 Gy) to the margin of involved vasculature does not substantially increase GI‐OAR doses if the boosting area is away from GI‐OARs (1 cm in the current study). This result agrees with recent investigations on this strategy, opening the way for achieving a greater regression in this critical area of the tumor …”
Section: Discussionsupporting
confidence: 93%
“…For that matter, the tumor area close to vascular structures, or involving them, is considered as a region of complex anatomy for GTV delineation, requiring very accurate guidelines for volume definition, and a central benchmark contour review could be indicated for prospective clinical trials concerning SBRT in pancreatic cancer. A comprehensive radiotherapy quality assurance program to ensure consistency in target definition and radiotherapy delivery has been shown to reduce variation in target volume definition [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, it became evident that soft tissue discrimination on these non-contrasted scans was poor, subsequently resulting in inconsistent ITV contours, even when performed by the same physician. Published studies of inter-physician contouring variability also illustrate this point (12), and MRI-based planning has been shown to result in smaller contours than CT-based planning (13).…”
Section: Discussionmentioning
confidence: 94%